2019
DOI: 10.1002/chem.201902131
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Route Toward Tetrazoles: The Thermolysis of Geminal Diazides

Abstract: A new synthetic route toward the tetrazole core is described, which is based on a general fragmentation pattern that was found in a range of compounds featuring geminal diazido units. Through a simple two‐step procedure, the synthesis of structurally diverse target compounds containing a tetrazole, such as tetrazoloquinoxalinones, benzoylaryltetrazoles, tetrazolotriazinones, and tetrazoloazepinones, was easily accomplished, starting from broadly accessible substrates (i.e., oxindoles, diarylethanones, pyrazolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…[7,8] Figure 1 shows a selection of commonly used organic azides in exemplary fields of application, as well as an example for the importance of geminal diazides in cyclisation reactions towards tetrazoles. [9] Some of the reasons for the attractiveness of the azido group in energetic materials are its thermodynamic properties, as it has a high positive heat of formation and adds about 260 kJ mol À 1 of endothermic energy to a carbon-based molecule. [10] In terms of developing more environmentally friendly and less toxic energetic materials, which has been of growing interest during the last decades, the azido group plays an important role, as it exclusively releases nitrogen gas during decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Figure 1 shows a selection of commonly used organic azides in exemplary fields of application, as well as an example for the importance of geminal diazides in cyclisation reactions towards tetrazoles. [9] Some of the reasons for the attractiveness of the azido group in energetic materials are its thermodynamic properties, as it has a high positive heat of formation and adds about 260 kJ mol À 1 of endothermic energy to a carbon-based molecule. [10] In terms of developing more environmentally friendly and less toxic energetic materials, which has been of growing interest during the last decades, the azido group plays an important role, as it exclusively releases nitrogen gas during decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Cu(II)‐catalyst [Cu−Cr−Al] was employed for the preparation of tetrazoles labelled with the positron emitter 13 N [22] . The report is available for transformation of geminal diazides to tetrazole by thermolysis from non‐nitrogenous substrates [23] …”
Section: Microwave‐assisted Chemistry Of Poly‐aza‐heterocyclesmentioning
confidence: 99%
“…The synthesis of diazidopyrazolone 2a was published recently. 8 4,4-Diazido-1,3-diphenyl-1H-pyrazol-5(4H)-one (3g). According to general procedure A using 150 mg of 0.635 mmol 1,3-diphenyl-1Hpyrazol-5(4H)-one (2g), 4,4-diazido-1,3-diphenyl-1H-pyrazol-5(4H)one (98.7 mg, 0.311 mmol, 49%) (3g) was obtained as a red solid after chromatography (CH → CH/DCM 1:1).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In the last few years, we are highly involved in studying the synthesis and reactivity of small organic molecules possessing geminal diazido units. In this context, we looked into the synthesis of tetrazolotriazinones 4 through the thermolysis of 4,4-diazidopyrazolones 3 (Scheme ), and it was found that the yields for the formation of the geminal diazides 3 through oxidative diazidation of the 1 H -pyrazol-5­(4 H )-ones 2 were surprisingly low, although our standard reaction conditions with iodine and sodium azide in aqueous dimethyl sulfoxide (DMSO) had been widely successful with many related substrate classes: under typical aqueous work-up conditions using Na 2 S 2 O 3 as the reductive agent to quench the excess of iodine, most of the initially generated diazido compound 3 was lost and deeply red-colored phases were obtained, instead. The careful analysis of the colored phases lets us assume that the color originates from the relatively smooth conversion of diazide 3 into the rubazonic acids 1 , under reductive work-up conditions.…”
Section: Introductionmentioning
confidence: 99%